Exposure to polybrominated biphenyl (PBB) associates with genome-wide DNA methylation differences in peripheral blood. Issue 1 (2nd January 2019) - Curtis, Sarah W.; Cobb, Dawayland O.; Kilaru, Varun; Terrell, Metrecia L.; Kennedy, Elizabeth M.; Marder, M. Elizabeth; Barr, Dana Boyd; Marsit, Carmen J.; Marcus, Michele; Conneely, Karen N.; Smith, Alicia K.
ABSTRACT: In 1973, Michigan residents were exposed to polybrominated biphenyl (PBB) when it was accidentally added to farm animal feed. Highly exposed individuals and their children have experienced endocrine-related health problems, though the underlying mechanism behind these remains unknown. We investigated whether PBB exposure is associated with variation in DNA methylation in peripheral blood samples from 658 participants of the Michigan PBB registry using the MethylationEPIC BeadChip, as well as investigated what the potential function of the affected regions are and whether these epigenetic marks are known to associate with endocrine system pathways. After multiple test correction (FDR <0.05), 1890 CpG sites associated with total PBB levels. These CpGs were not enriched in any particular biological pathway, but were enriched in enhancer and insulator regions, and depleted in regions near the transcription start site or in CpG islands (p < 0.05). They were also more likely to be in ARNT and ESR2 transcription factor binding sites (p = 3.27e-23 and p = 1.62e-6, respectively), and there was significant overlap between CpGs associated with PBB and CpGs associated with estrogen (p < 2.2e-16). PBB-associated CpGs were also enriched for CpGs known to be associated with gene expression in blood (eQTMs) (p < 0.05). These eQTMs were enriched for pathways related to immune function and endocrine-related autoimmune disease (FDR <0.05). These results indicate that exposure to PBB is associated with differences in epigenetic marks that suggest that it is acting similarly to estrogen and is associated with dysregulated immune system pathways.